(untitled) (Jurnal Pendidikan Fisika, 2020)
The research on the use of the LCMT model aims to find out the increase in teaching confidence, attitudes toward the teaching profession, and pedagogical content knowledge (PCK) competencies of students. The sampling technique uses purposive sampling and the number of individuals is 31 people consisting of 22 women and 9 men. Data obtained through questionnaires and assessment rubrics and tests. Questionnaires are used to measure teaching confidence and attitudes toward teaching profession. Assessment rubrics and tests are used to measure PCK. . Data were analyzed for normalized gain and paired t-test (paired sample test). The results showed a significant increase in teaching confidence with gain = 0.535 and t = 12.336 with sig. (2-tailed) = 0,000 (p <0.05), attitudes toward the teaching profession with gain = 0.565 and t = 8.3354 with sig (2-tailed) = 0,000 (p <0.05), and PCK with gain = 0.580 and t = 16.073 with sig (2-tailed) = 0,000 (p <0.05).